Answer
Verified
460.8k+ views
Hint: In this question, we will proceed by differentiating on both sides w.r.t ‘\[x\]’ by using the product rule of differentiation. Then simplify further by grouping and cancelling the common terms to prove the given equation.
Complete step-by-step answer:
Let the given equation be ${x^3}{y^5} = {\left( {x + y} \right)^8}............................................\left( 1 \right)$
Differentiating equation (1) w.r.t ‘$x$’ on both sides, we have
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^3}{y^5}} \right) = \dfrac{d}{{dx}}{\left( {x + y} \right)^8}\]
By product rule we have \[\dfrac{d}{{dx}}\left[ {f\left( x \right)g\left( y \right)} \right] = g\left( y \right)\dfrac{{df\left( x \right)}}{{dx}} + f\left( x \right)\dfrac{{dg\left( y \right)}}{{dx}}\]. So, using product rule we have
\[ \Rightarrow {y^5}\dfrac{d}{{dx}}\left( {{x^3}} \right) + {x^5}\dfrac{d}{{dx}}\left( {{y^5}} \right) = \dfrac{d}{{dx}}{\left( {x + y} \right)^8}\]
We know that \[\dfrac{d}{{dx}}\left( {{x^n}} \right) = n{x^{n - 1}}\]. By using this formula, we have
\[
\Rightarrow {y^5}\left( {3{x^2}} \right) + {x^3}\left( {5{y^4}\dfrac{{dy}}{{dx}}} \right) = 8{\left( {x + y} \right)^7}\left[ {\dfrac{d}{{dx}}\left( {x + y} \right)} \right] \\
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7}\left[ {\dfrac{d}{{dx}}\left( x \right) + \dfrac{d}{{dx}}\left( y \right)} \right] \\
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7}\left[ {1 + \dfrac{{dy}}{{dx}}} \right] \\
\]
Simplifying further, we have
\[
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} + 8{\left( {x + y} \right)^7}\dfrac{{dy}}{{dx}} \\
\Rightarrow \left( {5{x^3}{y^4} - 8{{\left( {x + y} \right)}^7}} \right)\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} - 3{x^2}{y^5}.................................................\left( 2 \right) \\
\]
From equation (1) we have
\[
\Rightarrow {x^3}{y^5} = {\left( {x + y} \right)^8} \\
\Rightarrow {x^3}{y^4} = \dfrac{{{{\left( {x + y} \right)}^8}}}{y}..........................................\left( 3 \right) \\
\]
Also, from equation (1), we have
\[
\Rightarrow {x^3}{y^5} = {\left( {x + y} \right)^8} \\
\Rightarrow {x^2}{y^5} = \dfrac{{{{\left( {x + y} \right)}^8}}}{x}..........................................\left( 4 \right) \\
\]
Substituting equation (3) and (4) in equation (2), we have
\[ \Rightarrow \left( {5\dfrac{{{{\left( {x + y} \right)}^8}}}{y} - 8{{\left( {x + y} \right)}^7}} \right)\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} - 3\dfrac{{{{\left( {x + y} \right)}^8}}}{x}\]
Grouping and cancelling the common terms, we have
\[
\Rightarrow {\left( {x + y} \right)^7}\left( {5\dfrac{{\left( {x + y} \right)}}{y} - 8} \right)\dfrac{{dy}}{{dx}} = {\left( {x + y} \right)^7}\left[ {8 - 3\dfrac{{\left( {x + y} \right)}}{x}} \right] \\
\Rightarrow {\left( {x + y} \right)^7}\left( {\dfrac{{5x + 5y - 8y}}{y}} \right)\dfrac{{dy}}{{dx}} = {\left( {x + y} \right)^7}\left[ {\dfrac{{8x - 3x - 3y}}{x}} \right] \\
\Rightarrow \left( {\dfrac{{5x - 3y}}{y}} \right)\dfrac{{dy}}{{dx}} = \left[ {\dfrac{{5x - 3y}}{x}} \right] \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{5x - 3y}}{x} \times \dfrac{y}{{5x - 3y}} \\
\therefore \dfrac{{dy}}{{dx}} = \dfrac{y}{x} \\
\]
Hence proved.
Note: Product rule of differentiation states the if the functions \[f\left( x \right)\] and \[g\left( y \right)\] are differentiable then \[\dfrac{d}{{dx}}\left[ {f\left( x \right)g\left( y \right)} \right] = g\left( y \right)\dfrac{{df\left( x \right)}}{{dx}} + f\left( x \right)\dfrac{{dg\left( y \right)}}{{dx}}\]. In these types of questions, try to solve the differentiation in a simpler way by not expanding the powers of the variables.
Complete step-by-step answer:
Let the given equation be ${x^3}{y^5} = {\left( {x + y} \right)^8}............................................\left( 1 \right)$
Differentiating equation (1) w.r.t ‘$x$’ on both sides, we have
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^3}{y^5}} \right) = \dfrac{d}{{dx}}{\left( {x + y} \right)^8}\]
By product rule we have \[\dfrac{d}{{dx}}\left[ {f\left( x \right)g\left( y \right)} \right] = g\left( y \right)\dfrac{{df\left( x \right)}}{{dx}} + f\left( x \right)\dfrac{{dg\left( y \right)}}{{dx}}\]. So, using product rule we have
\[ \Rightarrow {y^5}\dfrac{d}{{dx}}\left( {{x^3}} \right) + {x^5}\dfrac{d}{{dx}}\left( {{y^5}} \right) = \dfrac{d}{{dx}}{\left( {x + y} \right)^8}\]
We know that \[\dfrac{d}{{dx}}\left( {{x^n}} \right) = n{x^{n - 1}}\]. By using this formula, we have
\[
\Rightarrow {y^5}\left( {3{x^2}} \right) + {x^3}\left( {5{y^4}\dfrac{{dy}}{{dx}}} \right) = 8{\left( {x + y} \right)^7}\left[ {\dfrac{d}{{dx}}\left( {x + y} \right)} \right] \\
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7}\left[ {\dfrac{d}{{dx}}\left( x \right) + \dfrac{d}{{dx}}\left( y \right)} \right] \\
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7}\left[ {1 + \dfrac{{dy}}{{dx}}} \right] \\
\]
Simplifying further, we have
\[
\Rightarrow 3{x^2}{y^5} + 5{x^3}{y^4}\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} + 8{\left( {x + y} \right)^7}\dfrac{{dy}}{{dx}} \\
\Rightarrow \left( {5{x^3}{y^4} - 8{{\left( {x + y} \right)}^7}} \right)\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} - 3{x^2}{y^5}.................................................\left( 2 \right) \\
\]
From equation (1) we have
\[
\Rightarrow {x^3}{y^5} = {\left( {x + y} \right)^8} \\
\Rightarrow {x^3}{y^4} = \dfrac{{{{\left( {x + y} \right)}^8}}}{y}..........................................\left( 3 \right) \\
\]
Also, from equation (1), we have
\[
\Rightarrow {x^3}{y^5} = {\left( {x + y} \right)^8} \\
\Rightarrow {x^2}{y^5} = \dfrac{{{{\left( {x + y} \right)}^8}}}{x}..........................................\left( 4 \right) \\
\]
Substituting equation (3) and (4) in equation (2), we have
\[ \Rightarrow \left( {5\dfrac{{{{\left( {x + y} \right)}^8}}}{y} - 8{{\left( {x + y} \right)}^7}} \right)\dfrac{{dy}}{{dx}} = 8{\left( {x + y} \right)^7} - 3\dfrac{{{{\left( {x + y} \right)}^8}}}{x}\]
Grouping and cancelling the common terms, we have
\[
\Rightarrow {\left( {x + y} \right)^7}\left( {5\dfrac{{\left( {x + y} \right)}}{y} - 8} \right)\dfrac{{dy}}{{dx}} = {\left( {x + y} \right)^7}\left[ {8 - 3\dfrac{{\left( {x + y} \right)}}{x}} \right] \\
\Rightarrow {\left( {x + y} \right)^7}\left( {\dfrac{{5x + 5y - 8y}}{y}} \right)\dfrac{{dy}}{{dx}} = {\left( {x + y} \right)^7}\left[ {\dfrac{{8x - 3x - 3y}}{x}} \right] \\
\Rightarrow \left( {\dfrac{{5x - 3y}}{y}} \right)\dfrac{{dy}}{{dx}} = \left[ {\dfrac{{5x - 3y}}{x}} \right] \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{5x - 3y}}{x} \times \dfrac{y}{{5x - 3y}} \\
\therefore \dfrac{{dy}}{{dx}} = \dfrac{y}{x} \\
\]
Hence proved.
Note: Product rule of differentiation states the if the functions \[f\left( x \right)\] and \[g\left( y \right)\] are differentiable then \[\dfrac{d}{{dx}}\left[ {f\left( x \right)g\left( y \right)} \right] = g\left( y \right)\dfrac{{df\left( x \right)}}{{dx}} + f\left( x \right)\dfrac{{dg\left( y \right)}}{{dx}}\]. In these types of questions, try to solve the differentiation in a simpler way by not expanding the powers of the variables.
Recently Updated Pages
Fill in the blanks with suitable prepositions Break class 10 english CBSE
Fill in the blanks with suitable articles Tribune is class 10 english CBSE
Rearrange the following words and phrases to form a class 10 english CBSE
Select the opposite of the given word Permit aGive class 10 english CBSE
Fill in the blank with the most appropriate option class 10 english CBSE
Some places have oneline notices Which option is a class 10 english CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
When was Karauli Praja Mandal established 11934 21936 class 10 social science CBSE
Which are the Top 10 Largest Countries of the World?
What is the definite integral of zero a constant b class 12 maths CBSE
Why is steel more elastic than rubber class 11 physics CBSE
Distinguish between the following Ferrous and nonferrous class 9 social science CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE